Argumentation about Exchanges Values in Multiagent Systems and Collaborative Environments - Franco, Márcia Häfele Islabão; Costa, Antônio Carlos da Rocha (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2007)
This article shows how dialogue protocols can be used to support argumentation about the exchange values that may be involved in interactions that occur between agents, human or artificial. In consequence, the agents become able to influence each other’s assignment of values to the results of interactions, and such valuative process becomes much more liable to be influenced by issues such as emotions and social power, which may arise between agents during their social lives.